Toleransi Beberapa Genotipe Gandum (Triticum aestivum L.) Terhadap Kekeringan pada Stadia Perkecambahan - Firdausya, Andina Fabrini; Khumaida, Nurul; Ardie, dan Sintho Wahyuning (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTDrought is a major abiotic stress impeding wheat production world wide. Selection of potentially drought tolerant genotypes are necessary for wheat improvement. The objective of this study was to test the tolerance level of nine wheat genotypes to drought stress at germination stage. Assesment at germination stage using osmoticum solution is an effective method for selecting tolerant genotypes to drougt stress in a short period of time. The experiment was arranged on a randomized complete block design with two factors and three replications. The first factor was wheat genotype consisted of Nias, Selayar, Dewata, H-20, Munal, SBD, SBR, S-03, and YMH. The second factor was concentration of PEG 6000 consisted of 0, 5, 10, 15, and 20%. Observation variables were germination percentage, shoot length, root length, number of root, number of leaf, seedling fresh weight, and seedling dry weight. Increasing level of PEG concentration inhibited the growth of wheat seedling. Based on the highes R2 value on the regression analysis, relative root length can be used as selection character. Based on RD50 value of relative root length, 15% PEG was determined concentration to select drought tolerant on wheat genotypes. Nias genotype was identified as tolerant genotype, while SBD, S-03, YMH, and Munal were identified as drought sensitive genotypes.Keywords: abiotic stress, osmotic potential, Polyethylene Glycol, RD50, relative root length